2019
DOI: 10.1021/acsami.9b10706
|View full text |Cite
|
Sign up to set email alerts
|

Using Silver Nanoparticles-Embedded Silica Metafilms as Substrates to Enhance the Performance of Perovskite Photodetectors

Abstract: Plasmonic metal nanostructures provide a promising strategy for light trapping and therefore can dramatically enhance photocurrent in optoelectronics only if the trapped light can be coupled effectively from plasmons to excitons, whereas the reverse transfer of energy, charge, and heat from excitons to plasmons can be suppressed. Motivated by this, this work develops a scheme to implement a metafilm with Ag nanoparticles (NPs) embedded in 10 nm thick silica (Ag NPs–silica metafilm) to the active device channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…[7][8][9] Among the various contributions from the field of photonics proposed to improve light harvesting efficiency, photoemission, or other concomitant effects such as carrier dynamics, those based on the use of plasmonic resonances stand as the most widely explored. [10][11][12][13][14] In particular, numerous experimental works report the photovoltaic or photodetection performance enhancement that results from coupling metallic nanostructures to organic metal halide perovskite films. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] However, the origin of the improvement reported remains, in most cases, unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Among the various contributions from the field of photonics proposed to improve light harvesting efficiency, photoemission, or other concomitant effects such as carrier dynamics, those based on the use of plasmonic resonances stand as the most widely explored. [10][11][12][13][14] In particular, numerous experimental works report the photovoltaic or photodetection performance enhancement that results from coupling metallic nanostructures to organic metal halide perovskite films. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] However, the origin of the improvement reported remains, in most cases, unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we believe that, in our device, the surface plasmon resonance in the Ag NPs electrode is light excited and generates hot electrons via nonradiative decay plasmonic resonance, since the Ag NPs show a plasmonic resonance signal in the near-infrared region, as shown in Figure S3 in the supplementary file. The energy of the hot electrons may be greater than the small Schottky barrier between Ag NPs and MoS 2 , and it can be injected into the MoS 2 multilayer generating a photocurrent [57][58][59]. Additionally, the effect of the MoS 2 phases (1T and 2H) on the electrical performances of hybrid PDs was compared by Wang et al [60] and results indicated that the metallic 1T phase exhibited a high R value.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [153] Copyright 2019, American Chemical Society. mechanical stability and high-performance photodetection.…”
Section: Flexible Nanohybrid Photodetectors and Imagersmentioning
confidence: 99%
“…Plasmonic metal nanostructures may be placed in proximity to nanohybrids photodetectors for the benefit of light trapping. [ 153 ] A recent work by Alamri et al [ 154 ] combines the plasmonic effects from TMD nanodiscs grown on graphene and Ag nanoparticles deposited using an in vacuo process to obtain an enhanced photoresponse.…”
Section: Recent Progress In Nanohybrid Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation